Increasing the Infrastructure Access of Low-Income People in Peri-Urban of Bandung Metropolitan Area (International Journal of Built Environment and Sustainability, 2015)
Urbanization process occurred enormously in the last decade that increased urban population significantly. Rapid development caused by that process cannot be accommodated only by the core areas, particularly in the context of land availability. Facing this reality, peri-urban areas have been growing immensely. Peri-urban areas are those areas located beyond the core areas growth boundary and surrounded by the rural areas; therefore these areas are called as a gray area or transition region. Huge development of this area is one of the impacts of massive development of formal housing equipped by various types of infrastructure on one side without considering the existing infrastructure. On the other hand, the development of peri-urban area cannot be separated from growing numbers of informal housing for low-income groups who do not have access to the land in the core areas. Informal housings are generally not served by basic infrastructure. Infrastructure provision for low income people in peri-urban areas is not only generated by the problem of their economic condition, but also the problem of density, availability of land, and policy. That condition necessarily requires a scheme of specific solution for delivering basic infrastructure provision for those low-income groups in peri-urban area. The aim of this paper is formulating a model/scheme of basic infrastructure provision for low-income groups in peri-urban of Bandung Metropolitan Area (BMA) in order to increase community access to basic infrastructure. Method chosen in this study is descriptive and comparative analysis. This study recommends community-based model to be implemented in delivering infrastructure services for low-income groups.